Pengaruh Penyajian Dan Aksesibilitas Laporan Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Daerah - Syahrifa, Mayang; Ananda, Febryandhie; Zulvia, Dewi (Apik Cahaya Ilmu, 2025)
Accountability of regional financial management is the responsibility of the regional government in managing, using and reporting finances transparently and in accordance with laws and regulations to realize good governance. This study aims to explain the effect of financial report presentation and accessibility of regional financial reports on accountability of regional financial management at the Padang City Regional Financial and Asset Management Agency which is the objective of this study. The sample collection technique uses the total sampling method. The population in this study were employees or staff in the Secretariat Section, Budget Division, Asset Division, Accounting and Reporting Division and Treasury Division at the Padang City Regional Financial and Asset Management Agency. The sample used in this study amounted to 43 respondents. This study uses multiple linear regression analysis. The results of empirical research indicate that the presentation of financial reports and accessibility of regional financial reports have a positive and significant effect on accountability of regional financial management at the Padang City Regional Financial and Asset Management Agency.